Potent T cell agonism mediated by a very rapid TCR/pMHC interaction. - Boulter, J; Schmitz, N; Sewell, A; Godkin, A; Bachmann, M; Gallimore, A (2007)
The interaction between T cell receptors (TCR) and peptide-major histocompatibility complex (pMHC) antigens can lead to varying degrees of agonism (T cell activation), or antagonism. The P14 TCR recognises the lymphocytic choriomeningitis virus (LCMV)-derived peptide, gp33 residues 33-41 (KAVYNFATC), presented in the context of H-2D(b). The cellular responses to various related H-2D(b) peptide ligands are very well characterised, and P14 TCR-transgenic mice have been used extensively in models of virus infection, autoimmunity and tumour rejection. Here, we analyse the binding of the P14 soluble TCR to a broad panel of related H-2D(b)-peptide complexes by surface plasmon resonance, and compare this with their diverse cellular responses. P14 TCR binds H-2D(b)-gp33 with a KD of 3 microM (+/-0.5 microM), typical of an immunodominant antiviral TCR, but with unusually fast kinetics (k(off) = 1 s(-1)), corresponding to a half-life of 0.7 s at 25 degrees C, outside the range previously observed for murine agonist TCR/pMHC interactions. The most striking feature of these data is that a very short half-life does not preclude the ability of a TCR/pMHC interaction to induce antiviral immunity, autoimmune disease and tumour rejection.